2017
DOI: 10.1038/srep43018
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific N and P stoichiometry of Phragmites australis: geographic patterns and variation among climatic regions

Abstract: Geographic patterns in leaf stoichiometry reflect plant adaptations to environments. Leaf stoichiometry variations along environmental gradients have been extensively studied among terrestrial plants, but little has been known about intraspecific leaf stoichiometry, especially for wetland plants. Here we analyzed the dataset of leaf N and P of a cosmopolitan wetland species, Phragmites australis, and environmental (geographic, climate and soil) variables from literature and field investigation in natural wetla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…However, sample collection is commonly limited to a few individuals, a few populations, and averaged at the population or species level, disregarding the intraspecific variability [ 31 ]. Investigating the geographic variation within species can help uncover the mechanisms of relationships between plant tissue nutrients and environments [ 32 ] by excluding the confounding effects of taxonomic and phylogenetic structure such as those that have been found to influence the geographic patterns in leaf nutrients, and their linkages to climate and soil. Since relationships between environment and plant traits along environmental gradients could be presented as evidence of environmental control over species distribution, examining plant-environment (e.g., climate and soil nutrient availability) interactions may provide some insights into the underlying mechanisms of S. chamaejasme distribution in degraded grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…However, sample collection is commonly limited to a few individuals, a few populations, and averaged at the population or species level, disregarding the intraspecific variability [ 31 ]. Investigating the geographic variation within species can help uncover the mechanisms of relationships between plant tissue nutrients and environments [ 32 ] by excluding the confounding effects of taxonomic and phylogenetic structure such as those that have been found to influence the geographic patterns in leaf nutrients, and their linkages to climate and soil. Since relationships between environment and plant traits along environmental gradients could be presented as evidence of environmental control over species distribution, examining plant-environment (e.g., climate and soil nutrient availability) interactions may provide some insights into the underlying mechanisms of S. chamaejasme distribution in degraded grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the global leaf stoichiometry of coastal wetlands is still unclear (Lovelock et al., 2007). The recent research on inland and coastal wetlands has provided inconsistent results (Hu et al., 2017, 2018; Lovelock et al., 2007; Xia et al., 2014). For example, the leaf N content and N:P ratio in aquatic macrophytes decreased significantly with increasing latitude, whereas leaf P content increased with increasing latitude in inland wetlands of eastern China (Xia et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only a few studies have provided results showing significant differences in responses at different spatiotemporal scales. It has been shown that the leaf N concentrations and N:P of clonal plants decrease with increasing mean annual temperature ( Hu et al, 2017 ), and it was also found that leaf N and P increased significantly with increasing mean annual temperature ( Ying et al, 2015 ). Therefore, the study of the stoichiometric characteristics of individual modules of clonal plants can provide empirical results regarding resource acquisition and allocation trade-offs in response to heterogeneous conditions.…”
Section: Introductionmentioning
confidence: 99%